Enhanced nitrogen removal of single stage partial nitritation anammox system by glycine betaine addition at low temperature: Performance and mechanism. (October 2022) - Zhang, Menghan; Wang, Shaopo; Bi, Yanmeng; Meng, Fansheng; Wang, Dong; Qiu, Chunsheng; Wang, Chenchen; Yu, Jingjie
Abstract: Low activity of anaerobic ammonia oxidizing bacteria (AnAOB) at low temperature is still an obstacle to the application of a single stage partial nitritation anammox (SPNA) process. In order to improve the performance of nitrogen removal of this system at low ambient temperature, the glycine betaine (GB) was added into a continuous stirred tank reactor (CSTR) at 13–15 °C. At 15 °C, the nitrogen removal rate (NRR) was increased from 0.48 to 0.62 g N/(L·d) by adding 1 mM GB with the nitrogen loading rate of 0.81 g N/(L·d). The activity of hydrazine oxidase (HZO) was enhanced from 15.78 to 19.81 μmol Cyt-c/(g VSS·min), while the extracellular polymeric substances (EPS) production was reduced from 290.31 to 109.06 mg/g VSS after exogenous GB. When the temperature was <15 °C, however, the promoting effect of 1 mM GB was weakened, and the NRR was 0.43 g N/(L·d) at 13 °C. Increasing the addition of GB to 1.5 mM did not improve nitrogen removal performance at 13 °C, whereas it promoted the enrichment of heterotrophic bacteria (HB). Overall, results suggested GB had the potential to enhance the metabolic capability of AnAOB, which provided a novel strategy for improving the nitrogen removal performance of SPNA system at low temperature. Graphical abstract: Unlabelled Image